The Instructional Challenges and Opportunities for the Bangladeshi ESOL Teachers At Government Colleges During the COVID-19 Pandemic Period (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
During the Covid19 pandemic, all educational institutions including the government colleges of Bangladesh initiated online teaching with numerous challenges. From the two-year online education experiences, the ESOL teachers of Bangladesh learned many new skills and strategies and gathered some insights of online education that might be beneficial for future language teaching in Bangladesh. This study tried to explore the first-hand experience of the ESOL teachers at government colleges and their opinions about the opportunities derived from those experiences. This study followed a sequential explanatory method which is a mixed method of a quantitative method followed by a qualitative method. The findings of the study revealed that the teachers had to face many instructional challenges to teach the learners including the motivation of the learners and conducting E-assessment. The findings also highlighted that the teachers showed a positive attitude about their self-adaptation to the new ICT skills; their quality time with their family members; contribution of indoor physical exercises. In addition, the findings indicated some of the potential opportunities for future education including the ICT integration in language teaching, continuation of skill development, training on online pedagogy, and some suggestions for the policy makers.